The Influence of Pesantren Management, Kiai Skills, And Team Development On The Adaptation To Change Of Modern Islamic Boarding Schools In Riau Province - Jeka, Firdaus; Risnita; Mahmud MY (International Journal of Education, Language, and Social Science, 2025)
This study aims to examine the influence of pesantren management, kiai skills, and team development on change adaptation in Modern Islamic Boarding Schools in Riau Province. Change in pesantren is a necessity to adapt to the development of science and the demands of the times. The theory used in this study is the Work Team Effectiveness Model proposed by Danny Samson, Timothy Donnet, and Richard L. Daft, which emphasizes team effectiveness influenced by factors such as productive output, personal satisfaction, and the capacity to adapt and learn. This study proposes the hypothesis that there is an influence of pesantren management and kiai skills on team development and change adaptation partially, as well as a simultaneous influence between the three on change adaptation. This research method uses a quantitative approach with regression analysis to test the relationship between these variables. The results showed that pesantren management, kiai skills, and team development significantly influenced change adaptation in Modern Islamic Boarding Schools. This research is expected to contribute to the development of change management in Islamic educational institutions, especially pesantren, in facing the challenges of modernity.